Flavonol Profile Is a Reliable Indicator to Assess Canopy Architecture and the Exposure of Red Wine Grapes to Solar Radiation - Martínez-Lüscher, Johann; Brillante, Luca; Kurtural, Sahap Kaan (Frontiers in Plant Science, 2019)
Exposure to solar radiation is a determining factor of grape composition. Flavonol synthesis is upregulated by solar radiation leaving a fingerprint on flavonol profile. This study aimed to test the factors affecting flavonol accumulation and profile and their potential as an indicator to assess the overall exposure of red wine grape berry to solar radiation. We performed three experiments to study the response of flavonol accumulation and profile to (1) three different solar radiation exclusion treatments during berry development; (2) canopy porosity and plant area index (PAI); and (3) spatial variability of water status, vigor and ripening and cultural practices in commercial vineyards. Results showed a strong relationship between global radiation, inverse dormant pruning weights or canopy porosity (inversely proportional to PAI) and % kaempferol or % quercetin. Furthermore, the increase in concentration of the above two flavonols was associated with a reduction of % myricetin. Total flavonol content, % kaempferol, % quercetin and % myricetin had significant correlations with inverse dormant pruning weights, but these were less sensitive to over-ripening or water deficits. Flavonol profile was associated to site hydrology (wetness index) through changes in vigour, and to PAI; and responded to shoot thinning or fruit-zone leaf removal. These results support the reliability of the flavonol profile as an assessment parameter for studies aiming to discuss canopy architecture or the effect of solar radiation on grapevine berries.